KONSEP PENDIDIKAN HUMANIS MENURUT ALQURAN SURAH ALI IMRAN AYAT 112 DAN IMPLEMENTASINYA DALAM PROSES BELAJAR MENGAJAR - MR, RIFYAL LUTHFI (Asosiasi Mahasiswa Program Pascasarjana | Institut Agama Islam Darussalam | IAID | Ciamis | Jawa Barat, 2018)
The background in this thesis is the attitude of educators and learners who do not reflect themselves as human beings who must respect each other between humans with one another. As a result of the rapid influence of technological advances against educators and learners in particular, resulting in a lack of awareness of the nature of himself as a human being who must tolerate each other. From the above reasons, the author is interested to analyze the Qur'an Surah Ali Imran verse 112 which serve as a reference in finding the concept of humanist education. Thus, the researcher aims to explain the concept of humanist education according to Al Qur'an Surah Ali Imran verse 112 and its implementation in teaching and learning process of PAI. This research is a qualitative research by using literature review (library risearch). The primary data source used is the Qur'an interpretation of Ibnu Katsir, Al-Maraghi, Al-Misbah, Jalalin and secondary data are books that related to the discussion of this thesis. For data collection in writing using documentation method. And in the analysis of writing using content analysis (content analysis) that is an understanding conceptually sustainable in this thesis. The results of this study indicate that the concept of humanist education according to the munfasir Alquran Surah Ali Imran verse 112 in the learning process is: the concept of self-actualization, the concept of self in the real and ideal, the concept of self-motivation, and the concept of self-awareness. And the concept can be implemented by educators to learners well the earliest is to give each other a sense of love and affection after that must hold fast to the religion of Allah swt. It is well-connected between people who are Muslim and non-Muslim after they undergo religious freedom and have to tolerate each other or even respect each other even in a class or school there are people who are not Muslim. In addition to that the educator must also have the concept of teaching and learning that is appropriate with the planning, implementation, and evaluation. That way will cause implications or impacts positively and negatively for educators and learners in understanding and applying humanist education well in teaching and learning process until it does not have to happen things that are not desirable in education.